Swapping milk for electrolytes: investigating dairy calf activity and hunger after replacing a meal - Longer, Meredith; Woodrum Setser, Megan; Figueroa, Graciela; Renaud, David L.; Costa, Joao H. C.; Creutzinger, Katherine C. (Frontiers in Animal Science, 2025)
Replacing a milk meal with electrolytes is often done to hydrate pre-weaned calves following transport or diarrhea; however, its impact on the hunger and the activity of calves is unknown. Therefore, the objective of this study was to investigate the effect of replacing a milk feeding with electrolytes on the motivation of dairy calves to drink milk at a subsequent meal, the calf starter intake, and their activity. Healthy pre-weaned dairy calves (n = 100) were enrolled at 23 ± 1 days of age. This crossover study exposed all calves to two treatments over 2 weeks. Each calf received two milk (2.74 L) and two electrolyte (2.74 L of 252 mOSM/L solution) feedings in random order as their morning meal, with a washout period in between. To measure the motivation of calves to drink milk, calves who consumed at least 20% of their morning offered meal, whether milk or electrolytes, received either an unaltered milk replacer or a milk replacer with a bitter additive (0.35 g/L quinine hydrochloride dihydrate) as their evening meal. Over the 2-week study period, the calves were exposed to four daily combinations of treatment (electrolyte vs. milk as the morning meal) and test (bitter vs. regular milk as the evening meal) applications: electrolytes and bitter milk, electrolytes and regular milk, milk and bitter milk, and milk and regular milk. The treatment and test milk order was balanced by calf. The milk replacer, electrolyte, and calf starter quantities were weighed before and after feeding to determine the amount consumed by each calf. A random subset of calves (n = 69) was outfitted with accelerometers to measure the steps, the activity index, the lying time, and the lying bouts. These activity measures were summarized hourly for the 8 h between feedings on each test day. Regardless of the morning treatment, calves consumed less bitter milk than regular milk in the evening feeding, but an increase in calf willingness to consume bitter milk after replacing a meal with electrolytes was not observed. However, electrolyte-fed calves consumed more grain than milk-fed calves after the morning meal, took fewer steps, had a lower activity index, and spent less time lying at 7 and 8 h following the morning feeding compared with the milk-fed calves. The greater grain intake and less lying time during the hours before the evening feeding of the calves fed electrolytes in the morning compared with those fed milk suggest that substituting a milk meal with an electrolyte meal may increase behaviors indicating hunger in pre-weaned calves.